Tele-rehabilitation for Type II diabetics with heart failure with preserved ejection fraction - Yuan, Minjie; Xu, Haimin; Zhao, Dongqi; Shi, Dongdong; Su, Li; Zhu, Huifang; Lu, Shengdi; Wei, Junbo (Frontiers in Endocrinology, 2024)
Objective: This study aims to determine whether tele-rehabilitation has similar effects to conventional face-to-face physical rehabilitation for diabetic patients with heart failure with preserved ejection fraction (HFpEF). Materials and methods: Demographic, laboratory, diagnostic and rehabilitation information for patients with type 2 diabetes with HFpEF were extracted from disease-specific databases. Outcome measures, including the Short Physical Performance Battery (SPPB), 6-minute walk distance, frailty status, European Quality of Life 5-Dimension 5-Level questionnaire (EQ-5D-5L) and reduction in HbA1c from admission, patients who received tele-rehabilitation therapy were compared to those received face-to-face rehabilitation. Results: In this study, 90 patients with type 2 diabetes and HFpEF using tele-rehabilitation were matched with 90 patients with type 2 diabetes and HFpEF using face-to-face physical rehabilitation. Improvements in the results of the SPPB scores, 6-min walk distance and gait speed and EQ-5D-5L were noted from the follow-up time point 3 months to 6 months in both two groups. There were no significant differences in functional tests and quality of life between the two groups. Conclusion: Our study proved that mobile-based tele-rehabilitation programs are non-inferior to face-to-face physical rehabilitation for diabetes patients after HFpEF. In addition, adherence to the telerehabilitation program showed that the novel technology was accepted well and could be an alternative to the conventional face-to-face rehabilitation program.